REBRANDING POSAJA DALAM MEMBANGUN BRAND AWARENESS MELALUI INSTAGRAM @posaja.official - Wina Novita Rachmalia; Dedi Kurnia Syah Putra (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
This study explains how the strategy communication carried out by Pos Indonesia in the socialization of PosAja's rebranding. The socialization conducted through social media Instagram, this research was conducted because of the importance of socialization to build brand awareness from the public for PosAja. This research was carried out with qualitative approach, using the case study method. The data collection used is observation and interviews to obtain the results studied. Researchers will analyze strategies communication uses four stages. Getting to know the audience, compiling messages, establishing methods, and evaluation of communication. The results of this study indicate that the effective communication strategy running according to the four stages can be said to be appropriate. But the results on the evaluation that the socialization carried out still feels lacking and needs to improve how internal operating system that is done by the IT division. This needs to be done so that the products being developed is currently running according to the company's wishes, namely the wider community knows products from Pos Indonesia and the community uses the service in accordance with the vision and mission PosAja, which is to make those users a friend to a reliable friend in delivering goods to their destination.